13.4k views
1 vote
If f(x) = 3x-2 and g(x) =2x+1 find (f-g)(x)

2 Answers

4 votes
3x - 2 - 2x - 1

x - 3 the answer to the question
User David Yee
by
6.6k points
5 votes

Answer:

(f-g)(x) = x -3 .

Explanation:

Given : if f(x) = 3x-2 and g(x) =2x+1 .

To find : find (f-g)(x).

Solution : We have given f(x) = 3x-2 and g(x) =2x+1 .

(f-g)(x) = f(x) - g(x).

Now, plug the values of f(x) and g(x)

(f-g)(x) = 3x-2 - (2x+1 ).

(f-g)(x) = 3x -2 -2x -1.

Combine like terms

(f-g)(x) = 3x -2x -2 -1.

(f-g)(x) = x -3 .

Therefore, (f-g)(x) = x -3 .

User Jeremy Allen
by
6.3k points